NUMERICAL SIMULATION FOR LARGE UNCONTAINED ENGINE DEBRIS IMPACT AND PROTECTION METHODS - LI KeJun; PEI Yang; SONG BiFeng; YI HuaHui (Jixie qiangdu)
In order to evaluate the impact process induced by uncontained failure,numerical simulation for one-third HPT（ High Pressure Turbine） disk impact was carried out under different obliquity angles and residual fuel volumes in the wing structure. The study,which resulted in continuous dynamic response,focused on the interaction among debris,turbine cowl and integral fuel tank. The constitutive material mode and failure criteria proposed by Johnson-Cook were applied in solid element definition,while SPH（ Smooth Particle Hydrodynamics） model was used for fuel particles. The analysis involved the debris velocity history,fuel tank deformation along with the stress distribution changes during the whole process. It is shown from the results that with the increase of obliquity angle and residual fuel volume, the velocity loss and energy reduction rise correspondingly. The turbine cowl absorbs most of the debris energy while fuel also contributes to the absorption due to its viscidity. Hydrodynamic ram fails to cause lethal destruction of the tank structure under large debris impact. In the last part,fuel tank boundary design has been discussed qualitatively according to the simulation results.